OPTIMALISASI LAYANAN ONLINE PERPUSTAKAAN NASIONAL DI MASA PANDEMI COVID-19 - Dian Utami (VISI PUSTAKA: Buletin Jaringan Informasi Antar Perpustakaan, 2022)
The covid-19 pandemic has had a huge impact on the community, including libraries. The application of restrictions on physical activity outside the home is a challenge as well as an opportunity for the library to continue to provide services to the community. With various limitations, the library is required to innovate in serving the library to still be able to provide excellent service. This study aims to find out the innovation and utilization of the National Library of Indonesia's online services in the pandemic period. Through the optimization of digital services, the National Library has provided the widest access for all Indonesians to diverse and quality reading materials. The Covid-19 pandemic limited people's movements, but libraries have been shown to expand space virtually.